Level of Compliance with the Use of Amlodipine in Hypertensive Patients of Productive Age in Housing Dinari RT 01, Gresik) - Dwi Noviyanti, Nelita; Yulita Fazadini, Safira (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Hypertension was a disease that sufferers often did not realize they had, making it known as the silent killer. It was a leading cause of serious complications, such as heart attacks and strokes, and a major contributor to deaths from non-communicable diseases. Amlodipine was a medication used to treat hypertension, which worked by inhibiting calcium flow, helping to lower blood pressure. Although it was effective, its side effects, such as ankle swelling and headaches, could affect patient compliance. A preliminary survey revealed that most respondents only took the medication when they felt unwell. This study aimed to measure the level of compliance with amlodipine among productive-age hypertensive patients in the Dinari Housing Complex, RT 01, Gresik. A questionnaire was distributed via Google Form. The results showed that 91% of productive-age hypertensive patients had low compliance, 6% had moderate compliance, and 3% had high compliance.